CMOS oscillator design by using a metamaterial - based split ring resonator - Serttek, Özgün. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
High purity oscillators are of great importance in communication, radar, or med ical instrumentation systems. In today’s integrated circuit technology, low quality factor of inductors and capacitors deﬁne the limits of the phase noise of oscillators. In order to demonstrate an alternative to low quality resonators, this work pre sents a design of complementary cross coupled oscillator by using a metamaterial based Split Ring Resonator (SRR). SRRs having unique properties can exhibit very high quality factors which enable the design of low phase noise low power oscilla tor. Prior to oscillator design in this document, a lumped element model of SRR is also provided and veriﬁed with the measurement results. For demonstration, the pro posed complementary cross coupled oscillator by using SRR is designed using 180nm Silicon-On-Insulator (SOI) process which operates at 1.8GHz center frequency. Postlayout simulation results show that the oscillator phase noise is −179.5dBc/Hz and −180.8dBc/Hz at 100kHz and 1MHz oﬀset frequencies, relatively. The total power consumption is 8.1mW at 1.8V supply voltage.
Keywords: Resonators.; Nanostructured materials.; Oscillators, Electric.